2015
DOI: 10.1007/s12517-015-2173-0
|View full text |Cite
|
Sign up to set email alerts
|

The search for ‘hot shales’ in the western Kufra Basin, Libya: geochemical and mineralogical characterisation of outcrops, and insights into latest Ordovician climate

Abstract: Across the Saharan platform, mudrocks of latest Ordovician-Silurian age (the Tanezzuft Formation) are a major source rock interval for Palaeozoic petroleum systems, but source rock quality is variable and difficult to predict.In the Kufra Basin of southern Libya, evidence for organic enrichment in this formation is scarce. This paper presents the results of a spectral gamma-ray study of siliciclastic sedimentary rocks in Jabal Eghei at the western margin of the basin. The study spans the Ordovician-Silurian in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…This theory has been suggested in several published studies [e.g., Armstrong et al, 2005Armstrong et al, , 2009Le Heron et al, 2013]. It is also supported by the changes in clay mineral composition documented in the Kufra basin (Libya) by Meinhold et al [2015], who interpreted an increase in kaolinite content as probably representative of enhanced continental weathering due to the climate change occurring from the Late Ordovician icehouse to the Silurian greenhouse. Similarly, Finlay et al [2010] demonstrated an increase in continental weathering concomitant with the deglaciation based on osmium isotope analysis.…”
Section: Impact Of An Increased Nutrient Supply To the Oceansupporting
confidence: 53%
“…This theory has been suggested in several published studies [e.g., Armstrong et al, 2005Armstrong et al, , 2009Le Heron et al, 2013]. It is also supported by the changes in clay mineral composition documented in the Kufra basin (Libya) by Meinhold et al [2015], who interpreted an increase in kaolinite content as probably representative of enhanced continental weathering due to the climate change occurring from the Late Ordovician icehouse to the Silurian greenhouse. Similarly, Finlay et al [2010] demonstrated an increase in continental weathering concomitant with the deglaciation based on osmium isotope analysis.…”
Section: Impact Of An Increased Nutrient Supply To the Oceansupporting
confidence: 53%
“…This theory has been suggested in several published studies [e.g., Armstrong et al , , ; Le Heron et al , ]. It is also supported by the changes in clay mineral composition documented in the Kufra basin (Libya) by Meinhold et al [], who interpreted an increase in kaolinite content as probably representative of enhanced continental weathering due to the climate change occurring from the Late Ordovician icehouse to the Silurian greenhouse. Similarly, Finlay et al [] demonstrated an increase in continental weathering concomitant with the deglaciation based on osmium isotope analysis.…”
Section: The Early Silurian Rhuddanian Oceanic Anoxic Eventmentioning
confidence: 59%
“…They are the most important source rock for Early Palaeozoic-sourced hydrocarbons across North Africa (e.g., Lüning et al, 2000). Consequently, both the Upper Ordovician glaciogenic sediments and the lower Silurian 'hot' shales have been the focus of geological investigations in Libya (e.g., Lüning et al, 2000Lüning and Fello, 2008;Loydell et al, 2013;Meinhold et al, 2016;El Diasty et al, 2017a, b, c;Stockey et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Portable gamma-ray spectrometry (PGRS) is widely used to measure the U content of the Tanezzuft Formation shales at outcrop to search for 'warm' shales and 'hot' shales in southern Libya (e.g., Lüning and Fello, 2008;Meinhold et al, 2016).…”
Section: Introductionmentioning
confidence: 99%